The interval Zoro-symmetric single-step IZSS1-5D for the simultaneous bounding of real polynomial zeros - Wan Mohd Sham, Atiyah; Monsi, Mansor; Hassan, Nasruddin (Institute for Mathematical Research, Universiti Putra Malaysia, 2015)
A new modified method IZSS1-5D for the simultaneously bounding all the real zeros of a polynomial is formulated in this paper. The efficiency of this method is measured on the CPU times and the number of iterations after satisfying the convergence criteria where the results are obtained using five tested polynomials. The analysis performed shows that the R-order of convergence of this new procedure is at least five. The programming language used to obtain the numerical results is Matlab R2012, a software in association with Intlab V5.5 toolbox. The numerical results indicate that the procedure IZSS1-5D outperformed the IZSS1 in computational times and number of iterations.